A systematic review of peripheral nerve injury following laparoscopic colorectal surgery. (27th February 2013) - Codd, R. J.; Evans, M. D.; Sagar, P. M.; Williams, G. L.
Abstract Aim The risk of peripheral nerve injury associated with laparoscopic colorectal surgery has not been well established. We aimed to identify the number and type of peripheral nerve injuries associated with patient positioning in laparoscopic surgery. Method A systematic review of MEDLINE and Embase was undertaken of English and non‐English language articles. Search terms included the key words: laparoscopic, colorectal, nerve injury, nerve damage, brachial plexus, peripheral neuropathy, peripheral nerve injury, nerve and colonic injury. Articles were included where at least one peripheral nerve injury had been documented related to patient positioning at laparoscopic colorectal surgery. Data extraction for articles was conducted by two authors, using predefined data fields. Results Ten cases have been reported in the literature. All injuries involved the brachial plexus. They were associated with a lengthy procedure and abduction of the arm. Conclusion Although rare, the surgeon and theatre team must be aware of the risk of peripheral nerve injury when positioning patients for laparoscopic colorectal procedures.